Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation